First glimpse into the origin and spread of the Asian longhorned tick, Haemaphysalis longicornis, in the United States. (7th July 2020) - Egizi, Andrea; Bulaga‐Seraphin, Leslie; Alt, Erika; Bajwa, Waheed I.; Bernick, Joshua; Bickerton, Matthew; Campbell, Scott R.; Connally, Neeta; Doi, Kandai; Falco, Richard C.; Gaines, David N.; Greay, Telleasha L.; et al.
Abstract: Established populations of Asian longhorned ticks (ALT), Haemaphysalis longicornis, were first identified in the United States (US) in 2017 by sequencing the mitochondrial cytochrome c oxidase subunit I ( cox1 ) 'barcoding' locus followed by morphological confirmation. Subsequent investigations detected ALT infestations in 12, mostly eastern, US states. To gain information on the origin and spread of US ALT, we (1) sequenced cox1 from ALT populations across 9 US states and (2) obtained cox1 sequences from potential source populations [China, Japan and Republic of Korea (ROK) as well as Australia, New Zealand and the Kingdom of Tonga (KOT)] both by sequencing and by downloading publicly available sequences in NCBI GenBank. Additionally, we conducted epidemiological investigations of properties near its initial detection locale in Hunterdon County, NJ, as well as a broader risk analysis for importation of ectoparasites into the area. In eastern Asian populations (China/Japan/ROK), we detected 35 cox1 haplotypes that neatly clustered into two clades with known bisexual versus parthenogenetic phenotypes. In Australia/New Zealand/KOT, we detected 10 cox1 haplotypes all falling within the parthenogenetic cluster. In the United States, we detected three differentially distributed cox1 haplotypes from the parthenogenetic cluster, supporting phenotypic evidence that US ALT are parthenogenetic. While none of the source populations examined had all three US cox1 haplotypes, a phylogeographic network analysis supports a northeast Asian source for the US populations. Within the United States, epidemiological investigations indicate ALT can be moved long distances by human transport of animals, such as horses and dogs, with smaller scale movements on wildlife. These results have relevant implications for efforts aimed at minimizing the spread of ALT in the United States and preventing additional exotic tick introductions.